2021
DOI: 10.1016/j.radonc.2020.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes after external beam radiotherapy versus brachytherapy for palliation of dysphagia in esophageal cancer: A matched comparison of two prospective trials

Abstract: Background and purpose: A matched comparison of external beam radiotherapy (EBRT) versus brachytherapy recently demonstrated that EBRT appears at least as effective for palliating dysphagia in patients with incurable esophageal cancer. The aim of this analysis was to compare patient-reported outcomes (PROs) after EBRT versus brachytherapy. Materials and methods: In a multicenter prospective cohort study, patients with incurable esophageal cancer requiring palliation of dysphagia were included to undergo EBRT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Although intraluminal brachytherapy proved to be effective [ 14 ], it is more invasive and less widely implemented than external beam RT [ 9 , 19 , 20 ], with comparable efficacy [ 21 ]. Furthermore, patient-reported outcomes seem to favour external beam RT [ 22 ]. Short course palliative RT (20Gy in 5 fractions in consecutive workdays) was better tolerated with equal palliative effects than longer course [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although intraluminal brachytherapy proved to be effective [ 14 ], it is more invasive and less widely implemented than external beam RT [ 9 , 19 , 20 ], with comparable efficacy [ 21 ]. Furthermore, patient-reported outcomes seem to favour external beam RT [ 22 ]. Short course palliative RT (20Gy in 5 fractions in consecutive workdays) was better tolerated with equal palliative effects than longer course [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment options for dysphagia include stent placement, short-course radiotherapy, or systemic therapy [ 28 ]. If life expectancy is > 3 months, radiotherapy is recommended for palliation of dysphagia [ 29 31 ]. In our study, among patients who did not receive radiotherapy or placement of a stent for symptom control, dysphagia, odynophagia, and pain and discomfort improved during first-line therapy, although the improvements were smaller compared to the total population.…”
Section: Discussionmentioning
confidence: 99%
“…physical, role, social), loss of appetite, pain, and altered taste sensation, while those treated with EBRT had deterioration only in role functioning, and had a significant improvement in dysphagia and odynophagia. Comparison of both treatments revealed mostly comparable changes in PRO, but significantly favored EBRT in terms of nausea, vomiting, pain, and appetite loss [16]. In another study, Jeene et al compared the outcome with EBRT (5 fractions of 4 Gy) and intraluminal BT (single dose of 12 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study comparing brachytherapy (BT) and external beam radiotherapy (EBRT) reported that EBRT results in a significantly greater proportion of patients with improvement in dysphagia and smaller proportion of patients with severe toxicity [15]. Another study reported that EBRT resulted in significantly favorable outcomes, such as nausea, vomiting, pain, and appetite loss; however, both BT and EBRT resulted in a significantly improved QoL [16].…”
Section: Methodsmentioning
confidence: 99%